Carbon-coated lithium iron phosphate positive electrode material and application thereof

The carbon-coated lithium iron phosphate positive electrode material is prepared by the iron red method, controlling the carbon content and adjusting the material ratio, solving the problem of difficult control of electrochemical performance and preparation time in the prior art, and achieving high-performance and efficient preparation of positive electrode material.

CN119480955APending Publication Date: 2025-02-18CHONGQING TERUI NEW ENERGY MATERIALS CO LTD

Patent Information

Application Number
CN202411483887.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when preparing lithium iron phosphate positive electrode materials, it is difficult to effectively control the electrochemical performance and preparation time of the material, which affects the performance and production efficiency of lithium-ion batteries.

Method used

The carbon-coated lithium iron phosphate positive electrode material is prepared by the iron red method, the carbon content is controlled between 1.3% and 1.5%, the ratio of lithium iron phosphate to carbon coating is adjusted, and the preparation process is optimized to improve the electrochemical performance and preparation efficiency of the material. .

Benefits of technology

A carbon-coated lithium iron phosphate positive electrode material with excellent electrochemical performance has achieved a first-charge capacity of 158.9mAh/g, a 0.1Cg capacity of 156.4mAh/g, and a first-effect effect of 98.7%, while a preparation time is shortened by about 20%. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098223310000101
    Figure BDA0005098223310000101
  • Figure BDA0005098223310000102
    Figure BDA0005098223310000102
  • Figure BDA0005098223310000111
    Figure BDA0005098223310000111
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of battery positive electrode materials, and particularly relates to a carbon-coated lithium iron phosphate positive electrode material and application thereof. The preparation method of the positive electrode material comprises the following steps: (1) sintering a first preparation raw material for the first time to obtain lithium iron phosphate; wherein the first preparation raw materials comprise iron oxide, a phosphorus source, a lithium source and a first carbon source; (2) sintering the second preparation raw material for the second time to obtain the carbon-coated lithium iron phosphate positive electrode material; wherein the second preparation raw material comprises the lithium iron phosphate in the step (1) and a second carbon source; wherein the carbon content of the carbon-coated lithium iron phosphate positive electrode material is controlled to be 1.3%-1.5%. The carbon-coated lithium iron phosphate positive electrode material has excellent electrochemical performance, the first charge gram capacity can reach 158.9 mAh / g, the 0.1 C gram capacity can reach 156.4 mAh / g, and the first efficiency can reach 98.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery positive electrode material preparation, and specifically relates to a carbon-coated lithium iron phosphate positive electrode material and application thereof. Background Art

[0002] Since the advent of lithium-ion batteries in the early 1990s, they have been recognized as the most promising power and energy storage batteries due to their high energy density and good cycle performance. The preparation methods of lithium iron phosphate cathode materials, one of the key components of lithium-ion batteries, include high-temperature solid phase method, iron nitrate method, hydrothermal method, microwave heating method, sol-gel method and spray pyrolysis method.

[0003] Among them, the high-temperature solid-phase method is the mainstream lithium iron phosphate preparation method in the industry, which includes the ferric phosphate method, the ferrous oxalate method and the iron red method. Compared with other processes, the iron red method has the following advantages: (1) trivalent iron is used as the iron source, and the raw materials are cheap and easy to obtain; (2) the process and equipment are simple; (3) the introduction of a reducing agent (such as glucose or sucrose) can form a porous carbon film on the surface of the lithium iron phosphate particles, which enhances conductivity while preventing the particles from aggregating and growing; (4) no strict control is required to prevent Fe 2+ Oxidized, the cost is lower and it is easier to achieve large-scale industrial production.

[0004] Therefore, it is meaningful to develop a method for preparing carbon-coated lithium iron phosphate positive electrode materials using the iron red method. Summary of the invention

[0005] The present invention has developed a method for preparing a carbon-coated lithium iron phosphate positive electrode material using the iron red method. The present invention finds that the performance of the coated lithium iron phosphate positive electrode material can be controlled by controlling the carbon content of the carbon-coated lithium iron phosphate positive electrode material prepared by the iron red method.

[0006] In order to achieve the above purpose, the following technical solutions can be adopted:

[0007] On one hand, the present invention provides a carbon-coated lithium iron phosphate positive electrode material, (1) a first raw material is subjected to a first sintering to obtain lithium iron phosphate; wherein the first raw material comprises iron oxide, a phosphorus source, a lithium source and a first carbon source; (2) a second raw material is subjected to a second sintering to obtain a carbon-coated lithium iron phosphate positive electrode material; wherein the second raw material comprises the lithium iron phosphate described in step (1) and a second carbon source; wherein the carbon content of the carbon-coated lithium iron phosphate positive electrode material is controlled to be 1.3%-1.5%.

[0008] Preferably, the above preparation method can meet one or more combinations of the following conditions: (a) the first preparation raw material also includes a first dispersant; (b) the first preparation raw material also includes a first dispersant, and the first dispersant is selected from one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; (c) the phosphorus source is selected from one or more combinations of ammonium dihydrogen phosphate, phosphoric acid, and lithium dihydrogen phosphate; (d) the lithium source is selected from one or more combinations of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxalate; (e) the first carbon source is selected from one or more combinations of glucose or sucrose; (f) the molar ratio of Li, Fe and P in the lithium source, iron oxide and phosphorus source is (0.9-1.1):1:1; (g) the addition ratio of the first carbon source is a molar ratio of Fe:C=4:1; (h) in the mixture after the first dispersion, the particle size D50 is 0.4μm-1μm, and D90 is 2μm-5μm.

[0009] Preferably, the above preparation method can meet one or more combinations of the following conditions: (a) the second preparation raw material also includes a second dispersant; (b) the second preparation raw material also includes a second dispersant, and the second dispersant is selected from one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; (c) the second carbon source is selected from one or more combinations of glucose, sucrose or graphene; (d) the molar ratio of carbon to lithium iron phosphate in the second carbon source is (1-1.5):4; (e) in the mixture after the second dispersion, the particle size D50 is 1μm-1.5μm, and D90 is 3μm-5μm.

[0010] Preferably, the mass ratio of the second carbon source to the lithium iron phosphate in step (1) is (1:15)-(1:17).

[0011] Preferably, the above preparation method can also meet one or more combinations of the following conditions: (a) the inlet air temperature of the first atomization is 200℃-300℃, and the outlet air temperature is 50℃-150℃; (b) the temperature of the first sintering is 500℃-900℃; (c) the time of the first sintering is 2h-5h; (d) the first sintering is carried out under a protective gas environment; (e) the inlet air temperature of the second atomization is 300℃-400℃, and the outlet air temperature is 30℃-200℃; (f) the temperature of the second sintering is 400℃-800℃; (g) the time of the second sintering is 2h-6h; (h) the second sintering is carried out under a protective gas environment.

[0012] Preferably, the carbon content of the carbon-coated lithium iron phosphate positive electrode material is controlled to be 1.32%-1.44%.

[0013] Another aspect of the present invention provides a battery positive electrode sheet, which includes the carbon-coated lithium iron phosphate positive electrode material of the present invention.

[0014] Another aspect of the present invention provides a battery, which includes the battery positive electrode sheet of the present invention.

[0015] The beneficial effects of the present invention include at least:

[0016] (1) The present invention adjusts the carbon content in the carbon-coated lithium iron phosphate positive electrode material prepared by the iron oxide red method to 1.3%-1.5%, thereby obtaining a carbon-coated lithium iron phosphate positive electrode material with excellent electrochemical performance, wherein the first charge gram capacity can reach 158.9 mAh / g, the 0.1C gram capacity can reach 156.4 mAh / g, and the first efficiency can reach 98.7%.

[0017] (2) The present invention adjusts the ratio of lithium iron phosphate to carbon coating in detail and uses the secondary iron red method to prepare a carbon-coated lithium iron phosphate positive electrode material with good consistency and stability; and greatly shortens the time for preparing lithium iron phosphate (the cycle is shortened by about 20%). DETAILED DESCRIPTION

[0018] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.

[0019] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, materials, or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, materials, or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.

[0020] In order to achieve the above purpose, the following technical solutions can be adopted:

[0021] An embodiment of the present invention provides a carbon-coated lithium iron phosphate positive electrode material, (1) a first raw material is subjected to a first sintering to obtain lithium iron phosphate; wherein the first raw material comprises iron oxide, a phosphorus source, a lithium source and a first carbon source; (2) a second raw material is subjected to a second sintering to obtain a carbon-coated lithium iron phosphate positive electrode material; wherein the second raw material comprises the lithium iron phosphate in step (1) and a second carbon source; wherein the carbon content of the carbon-coated lithium iron phosphate positive electrode material is controlled to be 1.3%-1.5%.

[0022] It should be noted that the carbon coating (carbon encapsulation) will increase the conductivity of the positive electrode material, which will directly affect the transmission efficiency of electrons, thereby affecting the charge and discharge rate and cycle performance of the battery. The appropriate amount of carbon content can form an effective conductive network and promote the rapid conduction of electrons, thereby affecting the performance of lithium iron phosphate positive electrode materials.

[0023] In some specific examples, the above preparation method may satisfy one or more combinations of the following conditions:

[0024] (a) The first raw material further includes a first dispersant; specifically, during the first sintering, a dispersant (first dispersant) may be added to the first raw material for the first sintering to promote dispersion of the raw material for the subsequent reaction;

[0025] (b) the first preparation raw material further includes a first dispersant, which is selected from one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; specifically, the first dispersant in the present invention is a conventional dispersant in the art, preferably one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; more preferably polyethylene glycol, which achieves the best dispersion effect in the present invention;

[0026] (c) The phosphorus source is selected from one or more combinations of ammonium dihydrogen phosphate, phosphoric acid, and lithium dihydrogen phosphate; specifically, the phosphorus source in the present invention is a conventional phosphorus source in the art, preferably one or more combinations of ammonium dihydrogen phosphate, phosphoric acid, and lithium dihydrogen phosphate; more preferably ammonium dihydrogen phosphate, which is easy to react with a lithium source to form lithium dihydrogen phosphate, and the by-products are water and ammonia. Compared with other phosphorus sources, the reaction temperature required for ammonium dihydrogen phosphate during the synthesis process is lower, which helps to reduce energy consumption and improve production efficiency. Ammonium dihydrogen phosphate has good solubility in water and can be more evenly dispersed in the reaction system, improving the uniformity of the reaction and the consistency of the product. During the synthesis process, ammonium dihydrogen phosphate can promote the stability of the crystal structure of lithium iron phosphate, which helps to improve the cycle stability and capacity of the battery. The cost of ammonium dihydrogen phosphate is relatively low, which can reduce the production cost of lithium iron phosphate;

[0027] (d) the lithium source is selected from one or more combinations of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxalate; specifically, the lithium source in the present invention is a conventional lithium source in the art, preferably one or more combinations of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxalate; more preferably lithium hydroxide; lithium hydroxide has better electrochemical properties than other lithium sources (especially lithium carbonate) at high voltage, and can also be sintered at low temperature, so lithium hydroxide is preferred in the present invention;

[0028] (e) The first carbon source is selected from one or more combinations of glucose or sucrose; specifically, the first carbon source acts as a reducing agent to reduce iron oxide to divalent iron ions (Fe2+); the first carbon source in the present invention can be a carbon source known in the present invention, preferably one or more combinations of glucose or sucrose; more preferably glucose, which has a better reduction effect and the electrochemical performance of the subsequently prepared carbon-coated lithium iron phosphate cathode material is better;

[0029] (f) The molar ratio of Li, Fe and P in the lithium source, iron oxide and phosphorus source is (0.9-1.1):1:1; specifically, the ratio of the lithium source, iron oxide and phosphorus source in the present invention has an influence on the electrochemical properties of the prepared carbon-coated lithium iron phosphate positive electrode material. In the present invention, the molar ratio of Li, Fe and P in the lithium source, iron oxide and phosphorus source is preferably (0.9-1.1):1:1, such as 0.95:1:1, 1:1:1 or 1.05:1:1, etc.; more preferably 1:1:1, the carbon-coated lithium iron phosphate positive electrode material prepared by this ratio has better electrochemical properties;

[0030] (g) the first carbon source is added at a molar ratio of Fe:C=3.8-4.0:1; specifically, as described above, the first carbon source acts as a reducing agent, and its addition amount can be added according to the specific reaction conditions. In the present invention, the Fe:C addition ratio is 4.0;

[0031] (h) In the first dispersed mixture, the particle size D50 is 0.4μm-1μm, and D90 is 2μm-5μm; specifically, the particle size of the first prepared raw material after dispersion after mixing affects the first sintering reaction, thereby affecting the electrochemical properties of the prepared carbon-coated lithium iron phosphate positive electrode material; in the present invention, the particle size D50 is preferably 0.4μm-1μm, such as 0.5μm, 0.7μm, 0.8μm or 0.9μm, etc., and D90 is 2μm-5μm, such as 2μm or 3μm; more preferably D50 is 0.8μm, and D90 is 3.2μm.

[0032] It should be noted that in the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the preparation conditions can satisfy any one of conditions (a) to (h), and can satisfy two or more conditions at the same time, preferably satisfy two or more conditions at the same time, more preferably satisfy all conditions at the same time; more preferably, the preferred conditions of satisfying all conditions at the same time.

[0033] In some specific examples, the above preparation method may satisfy one or more combinations of the following conditions:

[0034] (a2) The second preparation raw material further includes a second dispersant; specifically, during the second sintering (carbon coating), in order to better disperse the lithium iron phosphate (powder) and the carbon source, a dispersant may be added to the lithium iron phosphate (powder) and the carbon source, which is more conducive to the dispersion of the lithium iron phosphate (powder) and the carbon source, and is also conducive to subsequent sintering;

[0035] (b2) the second preparation raw material further includes a second dispersant, which is selected from one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; specifically, the second dispersant is a conventional dispersant in the art, preferably one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; more preferably polyethylene glycol, which achieves the best dispersion effect in the present invention;

[0036] (c2) the second carbon source is selected from one or more combinations of glucose, sucrose or graphene; specifically, the second carbon source is used to provide carbon-coated carbon, which can be all organic carbon or inorganic carbon known in the art. In the present invention, one or more combinations of glucose, sucrose or graphene are preferred; more preferably, glucose is used as the carbon-coated carbon in the present invention, and the coating effect and the electrochemical performance of the prepared carbon-coated lithium iron phosphate positive electrode material are better;

[0037] (d2) The molar ratio of carbon in the second carbon source to lithium iron phosphate is (1-1.5):4; specifically, the carbon content of the prepared carbon-coated lithium iron phosphate positive electrode material is different due to different addition ratios of the second carbon source to lithium iron phosphate. In order to achieve the carbon content of 1.3%-1.5% in the present invention, in addition to optimizing different processes, the molar ratio of carbon in the second carbon source to lithium iron phosphate also has an impact. In the present invention, (1-1.5):4 is selected, such as 1.2:4, 1.3:4 or 1.4:4.

[0038] (e2) In the mixture dispersed for the second time, the particle size D50 is 1μm-1.5μm, and D90 is 3μm-5μm; specifically, the particle size of the second prepared raw material after dispersion after mixing affects the second sintering reaction (carbon coating), thereby affecting the electrochemical properties of the prepared carbon-coated lithium iron phosphate positive electrode material; after the second dispersion in the present invention, the particle size is preferably: the particle size D50 is 1μm-1.5μm, such as 1.2μm, 1.3μm or 1.4μm, and D90 is 3μm-5μm, such as 3.5μm, 4μm or 4.5μm; more preferably, D50 is 1.2μm and D90 is 3.5μm.

[0039] It should be noted that in the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the preparation conditions can satisfy any one of conditions (a2) to (e2), and can satisfy two or more conditions at the same time, preferably satisfy two or more conditions at the same time, more preferably satisfy all conditions at the same time; even more preferably, the preferred conditions of satisfying all conditions at the same time.

[0040] It should also be noted that in the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the preparation conditions can satisfy any one of conditions (a) to (h) and conditions (a2) to (e2), and can satisfy two or more conditions at the same time, preferably satisfy two or more conditions at the same time, more preferably satisfy all conditions at the same time; even more preferably, the preferred conditions of satisfying all conditions at the same time.

[0041] In some specific examples, the mass ratio of the second carbon source to the lithium iron phosphate in step (1) is (1:15)-(1:17), such as 1:16, 1:17 or 1:18.

[0042] In some specific examples, the above preparation method may also satisfy one or more combinations of the following conditions:

[0043] (a3) The air inlet temperature of the first atomization is 200°C-300°C, and the air outlet temperature is 50°C-150°C; specifically, the function of atomization is to improve the reaction efficiency and uniformity and optimize the drying effect; the atomization temperature has an influence on the atomization effect. In the present invention, the air inlet temperature of the atomization is preferably 200°C-300°C, such as 230°C, 250°C, 270°C or 290°C, and the air outlet temperature is 50°C-150°C, such as 80°C, 100°C or 120°C; more preferably, the air inlet temperature is 380°C and the air outlet temperature is 120°C;

[0044] (b3) The temperature of the first sintering is 500°C-900°C; specifically, in addition to atomization, the sintering temperature has an influence on the electrochemical properties of the prepared carbon-coated lithium iron phosphate positive electrode material, and in the present invention, it can be preferably 500°C-900°C, such as 550°C, 600°C, 670°C, 680°C, 690°C, 700°C, 750°C, 800°C, 850°C or 890°C, etc.;

[0045] (c3) the first sintering time is 3h-5h; specifically, the first sintering time can be 2h-5h, such as 2.5h, 3h, 3.5h, 4h or 4.5h;

[0046] (d3) the first sintering is performed in a protective gas environment; specifically, in order to reduce the occurrence of side reactions during the sintering process, it is preferred to perform the sintering in a protective gas environment, and the protective gas is well known in the art, such as nitrogen or an inert gas (helium or argon, etc.);

[0047] (e3) The inlet air temperature of the second atomization is 300°C-400°C, and the outlet air temperature is 30°C-200°C; similarly, the effect of the second atomization is the same as that of the first atomization, both of which are to improve the reaction efficiency and uniformity and optimize the drying effect; the conditions for the second atomization in the present invention are preferably that the inlet air temperature is 300°C-400°C, such as 320°C, 350°C or 370°C, and the outlet air temperature is 30°C-200°C, such as 50°C, 70°C, 100°C, 150°C or 170°C; more preferably, the inlet air temperature is 320°C and the outlet air temperature is 80°C;

[0048] (f3) The temperature of the second sintering is 400°C-800°C, such as 430°C, 480°C, 500°C, 550°C, 600°C, 650°C, 670°C, 710°C, 720°C, 730°C or 780°C, etc.; more preferably 720°C, the electrochemical performance of the prepared carbon-coated lithium iron phosphate positive electrode material is better;

[0049] (g3) The second sintering time is 2h-6h, such as 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or 5.5h, etc.; 3h is preferred in the present invention, so that a carbon-coated lithium iron phosphate positive electrode material with good electrochemical performance can be obtained in a shorter time;

[0050] (h3) The second sintering is performed under a protective gas environment; similarly, the second sintering is preferably performed under a protective gas environment; the protective gas is well known in the art, such as nitrogen or an inert gas (helium or argon, etc.);

[0051] It should be noted that in the preparation method of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the preparation conditions can satisfy any one of the conditions (a) to (k) and (a2) to (e2) and (a3) ​​to (h3), and can satisfy two or more conditions at the same time, preferably satisfy two or more conditions at the same time, more preferably satisfy all conditions at the same time; and more preferably, satisfy the optimal conditions of all conditions at the same time.

[0052] In some specific examples, the carbon content of the carbon-coated lithium iron phosphate positive electrode material may be 1.32%-1.44%, such as 1.32%, 1.35% or 1.44%.

[0053] It should be noted that those skilled in the art should know that the carbon-coated lithium iron phosphate positive electrode materials prepared by different preparation processes of carbon-coated lithium iron phosphate positive electrode materials have different requirements for carbon content in terms of electrochemical performance; the carbon content of the carbon-coated lithium iron phosphate positive electrode material prepared by the process of the present invention can preferably be 1.35%-1.5%, such as 1.4%, 1.45% or 1.48%, etc.; more preferably 1.35%, 1.32% or 1.44% in the present invention; for example, when the carbon content is 1.35%, the first charge gram capacity of the prepared carbon-coated lithium iron phosphate positive electrode material can reach 158.9mAh / g, and the 0.1C gram capacity can reach 158.9mAh / g. To reach 156.1mAh / g, the first efficiency can reach 98.23%; for example, when the carbon content is 1.32%, the first charge gram capacity of the prepared carbon-coated lithium iron phosphate positive electrode material can reach 158.6mAh / g, the 0.1C gram capacity can reach 156.4mAh / g, and the first efficiency can reach 98.6%; for example, when the carbon content is 1.44%, the first charge gram capacity of the prepared carbon-coated lithium iron phosphate positive electrode material can reach 158.2mAh / g, the 0.1C gram capacity can reach 156.3mAh / g, and the first efficiency can reach 98.7%; the electrochemical properties are better than those of other contents.

[0054] An embodiment of the present invention further provides a battery positive electrode sheet, which includes the carbon-coated lithium iron phosphate positive electrode material of the present invention.

[0055] It should be noted that, as described above, the carbon-coated lithium iron phosphate positive electrode material in the present invention has excellent electrochemical properties, and can be prepared into a battery positive electrode sheet by combining it with materials such as a conductive agent, a binder and a current collector (such as aluminum foil); in addition, the conductive agent, the binder and the current collector are all materials known in the art.

[0056] An embodiment of the present invention further provides a battery, which includes the battery positive electrode sheet of the present invention.

[0057] It should be noted that, based on the excellent electrochemical properties of the carbon-coated lithium iron phosphate positive electrode material in the present invention, the battery positive electrode sheet prepared therefrom can be assembled into a lithium iron phosphate battery; of course, it should be understood that the lithium iron phosphate battery also includes other components, such as an electrolyte, a negative electrode, a diaphragm or a battery shell, etc.; the electrolyte, the negative electrode, the diaphragm or the battery shell are all materials known in the art.

[0058] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.

[0059] Example 1

[0060] Lithium hydroxide, iron oxide and monoammonium phosphate (NH4H2PO4) are mixed in a molar ratio of 1:1:1, glucose and PEG (polyethylene glycol) (0.5% of the total mass of lithium hydroxide, iron oxide and monoammonium phosphate) with a molar ratio of Fe:C = 1:4 are added, and stirred for 1 hour, and the mixture is put into a ball mill at 600r / min for 3 hours to achieve a particle size of D50 = 0.8μm and D90 = 3.2μm, and then transferred to an atomization tower, and the inlet temperature is set to 380°C and the outlet temperature is set to 120°C. The mixed precursor is atomized, and the dried primary precursor is calcined at 680°C for 4 hours under argon conditions. The obtained material is crushed to obtain lithium iron phosphate powder.

[0061] Lithium iron phosphate powder was mixed with glucose and deionized water, and the mass ratio of glucose to lithium iron phosphate powder was 1:16.66. The mixed slurry was ball-milled for 1 hour, and the particle size was D50=1.2μm, D90=3.5μm. It was then atomized and dried, and the inlet temperature was set to 320℃ and the outlet temperature was set to 80℃ to obtain a dried secondary LFP / C precursor. The LFP / C precursor was calcined at 720℃ for 3 hours under argon conditions, and the sintered sample was crushed to obtain the LFP / C positive electrode material.

[0062] Example 2

[0063] The difference between Example 2 and Example 1 is that in Example 2, the mass ratio of glucose to lithium iron phosphate powder is 1:17.21, and the other steps are the same as in Example 1.

[0064] Example 3

[0065] The difference between Example 3 and Example 1 is that in Example 3, the mass ratio of glucose to lithium iron phosphate powder is 1:15.78, and the other steps are the same as in Example 1.

[0066] Example 4

[0067] The difference between Comparative Example 1 and Example 1 is that in Example 4, the mass ratio of glucose to lithium iron phosphate powder is 1:16.07, and the other steps are the same as in Example 1.

[0068] Example 5

[0069] The difference between Example 5 and Example 1 is that in Example 5, the mass ratio of glucose to lithium iron phosphate powder is 1:16.71, and the other steps are the same as in Example 1.

[0070] Comparative Example 1

[0071] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the mass ratio of glucose to lithium iron phosphate powder is 1:14.85, and the other steps are the same as in Example 1.

[0072] Comparative Example 2

[0073] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the mass ratio of glucose to lithium iron phosphate powder is 1:18.63, and the other steps are the same as in Example 1.

[0074] Comparative Example 3

[0075] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the mass ratio of glucose to lithium iron phosphate powder is 1:14.47, and the other steps are the same as in Example 1.

[0076] Comparative Example 4

[0077] Comparative Example 4 was prepared according to the method of patent publication CN112599730A, as follows:

[0078] (1) mixing lithium carbonate, iron powder and ammonium dihydrogen phosphate in a lithium: iron: phosphorus molar ratio of 1:1:1 to obtain a mixture, adding the mixture into water, performing a wet ball milling to obtain a slurry, drying and calcining the slurry at a calcination temperature of 300° C. for 3 h to obtain a lithium iron phosphate precursor;

[0079] (2) placing the lithium iron phosphate precursor obtained in step (1) in a mixed solution of glucose and ethanol and rapidly stirring; the stirring time is 3 hours and the stirring rate is 1000 revolutions per minute; the mass ratio of the glucose to the lithium iron phosphate precursor is 3:100; the mass ratio of the organic solvent to the lithium iron phosphate precursor is 8:10;

[0080] (3) ball milling the dispersion formed in step (2) to uniformly mix the raw materials; the ball milling speed is 2000 rpm and the dispersion time is 5 h;

[0081] (4) calcining the material obtained in step (3) at a high temperature in a mixed atmosphere of nitrogen and argon; the calcination temperature is 500° C. and the calcination time is 5 hours;

[0082] (5) Cooling the material calcined in step (4) in a mixed atmosphere of nitrogen and argon to obtain a carbon-coated lithium iron phosphate positive electrode material.

[0083] 2. Sample testing

[0084] (I) Carbon content test

[0085] The carbon content test method is determined in accordance with the determination method specified in GB / T 20123, including: testing by infrared carbon analyzer, weighing the sample at 0.2±0.01g, adding flux tungsten particles and pure iron flux, and then testing.

[0086] The carbon content of the LFP / C positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was tested, and the results are shown in Table 1 below.

[0087] Table 1 Carbon content of LFP / C positive electrode materials prepared in Examples and Comparative Examples

[0088] Example / Comparative Example Carbon content (%) Example 1 1.35 Example 2 1.32 Example 3 1.44 Example 4 1.36 Example 5 1.33 Comparative Example 1 1.53 Comparative Example 2 1.22 Comparative Example 3 1.57 Comparative Example 4 1.20

[0089] (II) Electrochemical performance test

[0090] Preparation and testing methods of button batteries: (Preparation of electrode sheets and button batteries: Add carbon-coated lithium iron phosphate powder: SP: PVDF in a mass ratio of 90:5:5 into a degassing tank, degas and stir to form a uniform slurry, use a coating machine to evenly coat the slurry on aluminum foil, dry it in a vacuum drying oven at 90°C for 16 hours, cut it and assemble CR2016 button batteries in a glove box) to test its electrochemical performance, and use the Blue Electric Battery Test System to perform constant current charge and discharge tests on the LiFePO4 / / Li system at room temperature. The test voltage range is 2V-3.75V; the specific process is: stand for 6 hours - constant current charging (0.1C) until the voltage reaches 3.75V - constant voltage charging until the current reaches 0.02C or the charging time exceeds half an hour - stand for 5 minutes - constant current discharge (0.1C) until the voltage reaches 2V - stand for 5 minutes - constant current charging (1C) until the voltage reaches 3.75V - constant voltage charging until the current reaches 0.02C or the charging time exceeds half an hour - constant current discharge (1C) until the voltage reaches 2V - stand for 5 minutes - end of test

[0091] The first charge gram capacity, 0.1C gram capacity and first efficiency of the LFP / C positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested according to the above-mentioned preparation and testing method. The results are shown in Table 2 below.

[0092] Table 2 Electrochemical properties of LFP / C positive electrode materials prepared in Examples and Comparative Examples

[0093]

[0094] (III) Other tests

[0095] In the following tests, particle size, specific surface area, tap density, compacted density, resistivity, main content and magnetic material content were tested according to the following methods:

[0096] Particle size test: measured according to the method specified in GB / T 19077.1;

[0097] Specific surface area test: The resistivity test is carried out according to the method for measuring the BET specific surface area of ​​powder by volumetric method specified in GB / T19587;

[0098] Tap density test: Measure according to the measurement method specified in GB / T5162;

[0099] Compacted density test: Determine according to the determination method specified in Appendix L of GB / T24533-2009;

[0100] Resistivity test: Test according to the test method specified in the general technical conditions for DC four-probe resistivity test in SJ / T 10314-1992;

[0101] Main content test: Determined according to the test method in GB / T 30835-2014 Carbon composite lithium iron phosphate positive electrode material for lithium ion batteries;

[0102] Magnetic material content test: Cover the magnet bar with a plastic bag, adsorb the magnetic material on the lithium iron phosphate powder, and weigh the mass of the magnetic material.

[0103] The particle size, specific surface area and resistivity of the LFP / C positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 3 below.

[0104] Table 3 Particle size, specific surface area and resistivity of LFP / C positive electrode materials prepared in Examples and Comparative Examples

[0105]

[0106]

[0107] In addition, the tap density and compacted density of the LFP / C positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were also tested, and the results are shown in Table 4 below.

[0108] Table 4 Tap density and compaction density of LFP / C positive electrode materials prepared in Examples and Comparative Examples

[0109] Example / Comparative Example Tap density Compacted density Example 1 0.87 2.42 Example 2 0.82 2.32 Example 3 0.83 2.34 Example 4 0.78 2.40 Example 5 0.86 2.32 Comparative Example 1 0.79 2.38 Comparative Example 2 0.85 2.44 Comparative Example 3 0.80 2.48 Comparative Example 4 0.81 2.38

[0110] In addition, the main content and magnetic substance content of the LFP / C positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were also tested (the magnetic impurities in the lithium iron phosphate material have an impact on the self-discharge of the battery, and the magnetic impurity content in the lithium iron phosphate material is proportional to the self-discharge rate of the battery, that is, the higher the magnetic impurity content of the material, the greater the self-discharge rate of the battery made therefrom). The results are shown in Table 5 below.

[0111] Table 5 Main content and magnetic substance content of LFP / C positive electrode materials prepared in Examples and Comparative Examples

[0112]

[0113]

[0114] It can be seen from Table 5 above that the magnetic substance content of Examples 1 to 3 and Example 5 is lower than that of Comparative Examples 1 to 4, and only the magnetic substance content of Example 4 is higher than that of Comparative Examples 1 to 4, but it also meets the production requirements.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.

Claims

1. A carbon-coated lithium iron phosphate positive electrode material, characterized in that: The preparation method comprises: (1) sintering the first raw material for the first time to obtain lithium iron phosphate; wherein the first raw material for the first preparation includes iron oxide, a phosphorus source, a lithium source and a first carbon source; (2) sintering the second prepared raw material for a second time to obtain a carbon-coated lithium iron phosphate positive electrode material; wherein the second prepared raw material comprises the lithium iron phosphate in step (1) and a second carbon source; Wherein, the carbon content of the carbon-coated lithium iron phosphate positive electrode material is controlled to be 1.3%-1.5%.

2. The carbon-coated lithium iron phosphate positive electrode material according to claim 1, characterized in that: The preparation method meets one or more combinations of the following conditions: (a) the first preparation raw material further includes a first dispersant; (b) the first preparation raw material further includes a first dispersant, and the first dispersant is selected from one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; (c) the phosphorus source is selected from one or more combinations of diammonium phosphate, phosphoric acid, and lithium dihydrogen phosphate; (d) the lithium source is selected from one or more combinations of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and lithium oxalate; (e) the first carbon source is selected from one or more combinations of glucose or sucrose; (f) the molar ratio of Li, Fe and P in the lithium source, iron oxide and phosphorus source is (0.9-1.1):1:1; (g) the first carbon source is added in a molar ratio of Fe:C=4:1; (h) In the mixture after the first dispersion, the particle size D50 is 0.4 μm-1 μm, and D90 is 2 μm-5 μm.

3. The carbon-coated lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The preparation method meets one or more combinations of the following conditions: (a) the second preparation raw material further includes a second dispersant; (b) the second preparation raw material further includes a second dispersant, which is selected from one or more combinations of polyethylene glycol, polyacrylic acid, polymethacrylic acid, hexamethyldisilazane trimethyl phosphate, polyvinyl alcohol or sodium dodecylbenzene sulfonate; (c) the second carbon source is selected from one or more combinations of glucose, sucrose or graphene; (d) the molar ratio of carbon in the second carbon source to lithium iron phosphate is (1-1.5):4; (e) In the mixture after the second dispersion, the particle size D50 is 1 μm-1.5 μm, and D90 is 3 μm-5 μm.

4. The carbon-coated lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The mass ratio of the second carbon source to the lithium iron phosphate in step (1) is (1:15)-(1:17).

5. The carbon-coated lithium iron phosphate positive electrode material according to claim 3, characterized in that: The mass ratio of the second carbon source to the lithium iron phosphate in step (1) is (1:15)-(1:17).

6. The carbon-coated lithium iron phosphate positive electrode material according to claim 1, 2 or 5, characterized in that: The preparation method meets one or more combinations of the following conditions: (a) The air inlet temperature of the first atomization is 200℃-300℃, and the air outlet temperature is 50℃-150℃; (b) The temperature of the first sintering is 500°C-900°C; (c) The first sintering time is 2h-5h; (d) The first sintering is carried out in a protective gas environment; (e) The air inlet temperature of the second atomization is 300°C-400°C, and the air outlet temperature is 30°C-200°C; (f) The temperature of the second sintering is 400°C-800°C; (g) The second sintering time is 2h-6h; (h) The second sintering is carried out under a protective gas environment.

7. The carbon-coated lithium iron phosphate positive electrode material according to claim 1, 2 or 5, characterized in that: The carbon content of the carbon-coated lithium iron phosphate positive electrode material is controlled to be 1.32%-1.44%.

8. The carbon-coated lithium iron phosphate positive electrode material according to claim 6, characterized in that: The carbon content of the carbon-coated lithium iron phosphate positive electrode material is controlled to be 1.32%-1.44%.

9. A positive electrode sheet for a battery, characterized in that: The invention comprises the carbon-coated lithium iron phosphate positive electrode material as described in any one of claims 1 to 8.

10. A battery, characterized in that Including the battery positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of carbon-coated lithium iron phosphate positive electrode material

    CN112599730A

Cited By

  • Lithium iron phosphate positive electrode material and preparation method thereof, positive plate, battery, battery pack and electric equipment

    CN121341986A

  • Step-by-step reduction coating preparation method and material of high-compaction lithium iron phosphate and lithium battery

    CN122393268A